Relationships between healthcare employees and managers as a resource for well-being at work. Issue 1 (1st January 2018) - Schön Persson, Sophie; Nilsson Lindström, Petra; Pettersson, Pär; Andersson, Ingemar; Blomqvist, Kerstin
ABSTRACT: Relationships at work are important to the psychosocial work environment and may be resources for the employees' well-being. There is a need for a better understanding of what generate positive relationships at work. The aim of the study was to gain a better understanding of the relationship between employees and managers in municipal healthcare. A qualitative study with twenty-seven individual interviews was conducted with healthcare employees and managers in municipal healthcare. The relationship between manager and employees and its possible contribution to well-being was a key focus. A comparison and tentative analysis, inspired by hermeneutics, was used in order to analyse similarities and differences in employee and manager experiences. The findings revealed similarities as well as considerable differences between employees and managers in their experiences. Two themes emerged from the interpretation of the text: (i) Health-promoting relationships are characterized by asymmetry and by a manager that stands outside the group; and (ii) Health-promoting relationships are characterized by mutuality and symmetry and by a manager that is part of the group. The relationship between the employees and the managers are both a resource for doing a good job and a means for achieving belongingness at work. To highlight well-working aspects of relationships at work, may contribute to a better psychosocial work environment and, ultimately, the well-being among healthcare recipients.